TINDAK TUTUR EKSPRESIF DALAM FILM SWEET 20 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMP - N, Syafika Maysara; Hikmat, Ade; Amalia, Nur (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the form and type of expressive speech acts in the Sweet 20 film and their implications for Indonesian language learning in junior high school. This research uses a descriptive-qualitative method. The data for this research is in the form of words, phrases, or sentences. The data source in this research is the Sweet 20 film produced by Starvision Plus and CJ Entertaimen. The data collection technique in this research uses observation and note-taking. Data analysis is done using the qualitative descriptive method by interpreting the data through words. The result shows that 73 data points in the Sweet 20 film that are expressive speech acts can be classified into 6 thanks, 5 apologies, 4 happiness utterances, 11 praising utterances, 3 complaining utterances, 41 angry utterances, 1 blaming utterance, and 2 expecting expressive utterances. The results of this study can be used as teaching materials for Indonesian language learning in junior high school.